Answer:
328.5
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
![-3\sqrt{2}+3\sqrt{8}= \\\\-3\sqrt{2}+3\sqrt{2\cdot 2^2}= \\\\-3\sqrt{2}+6\sqrt{2}= \\\\3\sqrt{2}](https://tex.z-dn.net/?f=-3%5Csqrt%7B2%7D%2B3%5Csqrt%7B8%7D%3D%20%5C%5C%5C%5C-3%5Csqrt%7B2%7D%2B3%5Csqrt%7B2%5Ccdot%202%5E2%7D%3D%20%5C%5C%5C%5C-3%5Csqrt%7B2%7D%2B6%5Csqrt%7B2%7D%3D%20%5C%5C%5C%5C3%5Csqrt%7B2%7D)
Hope this helps!
We want the final coordinate of K to become (-3,1). If you reflect across the y-axis, you transform
![(x,y)\mapsto(-x,y)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Cmapsto%28-x%2Cy%29)
So, we need to move K to (3,1), and then reflect it across the y-axis. Since K starts at (-1,4), we have to move it 4 units to the right and 3 units down.
Coordinate 1 is : (0,3)
Coordinate 2 is : (-4,-2)
Coordinate 3 is : (-1,-5)
Coordinate 4 is (4,0)
Hope this helps!